Are radical changes to health and social care paving the way for fewer services and new user charges?. (27th September 2017) - Sutaria, Shailen; Roderick, Peter; Pollock, Allyson M
Abstract : Current reforms to health and social care services, and radical redesign of the local government finance system, may signal the end of the NHS and local government in England as we know them, argue Shailen Sutaria, Peter Roderick, and Allyson M Pollock